2014
DOI: 10.2196/jmir.3200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Parent-Initiated Social Media Campaign for Hirschsprung’s Disease

Abstract: BackgroundSocial media can be particularly useful for patients or families affected by rare conditions by allowing individuals to form online communities across the world.ObjectiveOur aim in this study was to conduct a descriptive and quantitative analysis of the use of a social media community for Hirschsprung’s Disease (HD).MethodsIn July 2011, a mother of a child with HD launched the “Shit Happens” campaign. The campaign uses social media (blogs, Twitter, and Facebook) to engage other families affected by H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…Of the 98 research studies included in the review by Moorhead et al, 13 were using Facebook as a means of increasing awareness and communicating about a range of topics (eg, concussion, diabetes, breast cancer, attention-deficit/hyperactivity disorder) [13]. Facebook has also been used as part of a social media campaign intended to raise awareness for Hirschsprung disease and to connect and engage families affected by this rare condition [14]. While reach and responsiveness are considered strengths of social media usage, other studies have reported benefits of creating smaller communities.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 98 research studies included in the review by Moorhead et al, 13 were using Facebook as a means of increasing awareness and communicating about a range of topics (eg, concussion, diabetes, breast cancer, attention-deficit/hyperactivity disorder) [13]. Facebook has also been used as part of a social media campaign intended to raise awareness for Hirschsprung disease and to connect and engage families affected by this rare condition [14]. While reach and responsiveness are considered strengths of social media usage, other studies have reported benefits of creating smaller communities.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of performing new media campaigns has been shown for other topics like breastfeeding [14] , smoking cessation [15] , obesity and diabetes [16] , and Hirschsprungs's disease [17] . We report for the first time of a new media campaign in the field of urology.…”
Section: Discussionmentioning
confidence: 99%
“…[7] This initial work demonstrated that this community was highly responsive and the campaign helped to connect families across the globe. We then jointly developed the present study to complete a needs assessment via social media to prioritize information needs related to HD.…”
Section: "For a Family Affected By Hirschsprung's Disease (Hd) The Fmentioning
confidence: 99%